AKTIVITAS ANTIOKSIDAN DAN BIOAKTIVITAS IN VITRO EKSTRAK AIR DAN EKSTRAK ETANOL DAUN DAN RANTING BENALU Macrosolen cochinchinensis (Lour.) van Tiegh. PADA INANG NANGKA ( Artocarpus heterophyllus) - Nina Artanti; Akhmad Darmawan (Research Center for Chemistry - LIPI, 2009)
Study on antioxidant activity and bioactivity of water and ethanol extracts from the leaves and twigs of mistletoe (Macrosolen cochinchinensis (Lour.) Van Tiegh) that grew on jackfruit (Artocarpus heterophyllus) tree as the host have been conducted. Water extracts of the M. cochinchinensis leaves andtwigs were active as antioxidant with IC50 23.08 ug/mL dan 21.56 ug/mL respectively. Whereas the ethanol extracts of both leaves and twigs was not active because the ICso higher than 100 ug/mL (not active as antioxidant against DPPH). Both water and ethanol extracts of M. cochinchinensis leaves and twigs did not showed bioactivity against Artemia salina Leach brine shrimp with each extracts has LCso higher than 1000 pg/mL.Key words Antioxidant, Bioactivity, Macrosolen cochinchinensi (Lour.) van Tiegh., Artocarpus heterophyllus. Artemiasalina Leach.